2012
DOI: 10.1111/j.1574-6941.2012.01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of microorganism-invertebrate interactions on benthic nitrogen cycling

Abstract: Infaunal invertebrate activity can fundamentally alter physicochemical conditions in sediments and influence nutrient cycling. However, despite clear links between invertebrate activity and microbially mediated processes such as nitrification, the mechanisms by which bioturbating macrofauna affect microbial communities have received little attention. This study provides strong evidence for differential stimulation of microbial nitrogen transformations by three functionally contrasting species of macrofauna (He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 89 publications
3
58
0
Order By: Relevance
“…Over extended periods of time these physical and biogeochemical changes reduce habitat complexity (Kaiser et al 2002) and alter community structure by reconfiguring species and functional trait dominance (Kaiser et al 2006;Pusceddu et al 2014;Sciberras et al 2016), causing a shift from sessile emergent species with high biomass to smaller bodied infaunal species . Importantly, such selective forcing may skew trophic structure (Duffy 2003;Wohlgemuth et al 2016) and lead to the loss of species interactions that influence nutrient generation and dynamics (Gilbertson et al 2012); the active redistribution of particles and fluids by infaunal invertebrates, for example, directly contributes to the spatial and temporal heterogeneity of oxic and anoxic zones (Bertics and Ziebis 2009), the availability of organic matter (Levin et al 1997), and the distribution of metabolic electron acceptors (Aller 1982;Fanjul et al 2007) that are important in controlling microbial process rates and benthic-pelagic coupling linked to primary productivity (Lohrer et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Over extended periods of time these physical and biogeochemical changes reduce habitat complexity (Kaiser et al 2002) and alter community structure by reconfiguring species and functional trait dominance (Kaiser et al 2006;Pusceddu et al 2014;Sciberras et al 2016), causing a shift from sessile emergent species with high biomass to smaller bodied infaunal species . Importantly, such selective forcing may skew trophic structure (Duffy 2003;Wohlgemuth et al 2016) and lead to the loss of species interactions that influence nutrient generation and dynamics (Gilbertson et al 2012); the active redistribution of particles and fluids by infaunal invertebrates, for example, directly contributes to the spatial and temporal heterogeneity of oxic and anoxic zones (Bertics and Ziebis 2009), the availability of organic matter (Levin et al 1997), and the distribution of metabolic electron acceptors (Aller 1982;Fanjul et al 2007) that are important in controlling microbial process rates and benthic-pelagic coupling linked to primary productivity (Lohrer et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The bioturbation of epifauna can facilitate nutrient releases from sediment by molecular or eddy diffusion (Kristensen et al, 2012), possibly resulting in increases in NH + 4 concentration with snail density increasing. Gilbertson et al (2012) found that epifauna could increase N mineralization by shifting bacterial community structure due to grazing and/or mucus secretion. In the present study, DON was negatively correlated with snail density (Table 1) and NH + 4 (r = −0.84; P = 0.009), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the correlation between enrichment and macrofaunal density and species richness in sandy mud and the relative biomass of different functional groups in sand was unexpected (given the short time scale of the experiment) and most likely the result of stochastic variation in the abundance of infauna and unrelated to the enrichment treatment. However, in sandy sediments, organic matter enrichment correlated with a reduction in the variation and mean activity of bacterial denitrifiers (nirS), and in sandy mud sediments with a reduction in mean activity of archaeal denitrifiers (AnirKa), and a change in ammonia oxidiser community structure, altering the ratio of ammonia oxidising bacteria to ammonia oxidising archaea (as in Gilbertson et al 2012). An effect, however, was not found for all microbes measured, for example for the nitrifiers (AOB amoA, AOA amoA) and anammox (hzo) in either sand or sandy mud.…”
Section: Discussionmentioning
confidence: 99%
“…Over extended and repeated periods of fishing activity, changes in the functional composition of invertebrate communities can have a disproportionate influence on nutrient cycling through changes in the bioturbation potential of the benthic community (Duplisea et al 2001;Widdicombe et al 2004). The active redistribution of particles (bioturbation) and fluids (bioirrigation) by infaunal macro-invertebrates, such as bivalves, polychaetes and crustaceans, directly contributes to the spatial and temporal heterogeneity of oxic and anoxic zones (Bertics and Ziebis 2009), organic matter availability (Levin et al 1997) and the distribution of metabolic electron acceptors (Fanjul et al 2007) that are important in controlling microbial process rates (Gilbertson et al 2012;Laverock et al 2014). The close association between the macrobenthic invertebrate community composition and microbial activity suggests that a reduction in bioturbation potential of the benthic community ensuing from the loss or change in relative composition of invertebrate species associated with bottom fishing will lead to changes in microbial-mediated processes such as nitrification, denitrification and anammox.…”
mentioning
confidence: 99%